PENERAPAN DIAGRAM KONTROL T2 HOTELLING PADA PROSES PRODUKSI KACA - Muhammad Hilman Rizki Abdullah; Rita Rahmawati; Hasbi Yasin (Jurnal Gaussian, 2015)
SPC (Statistical Process Control) is a method used to monitoring the process of identifying the causes of variance and improve processes. In term of its variable characteristic, quality control in SPC can be divided into two kinds of univariate control charts and multivariate control charts. T2 Hotelling control chart is a multivariate control charts used in quality control process mean. In the process of glass production, This research was conducted in two stages by making use three major characteristics of quality, those are thickness, length and width. Application of T2 Hotelling control chart on the first phase of the signal are out of control, so it is necessary to identify the variable signal causes the uncontrolled use Decomposition MYT (Mason, Young and Tracy). Based on the identification of variables obtained that the variable width is the cause of the signal out of control. In the second phase is stable glass production process it shows the company has made improvements to the production process of phase II. Keywords: Statistical Process Control, Quality Control, Hotelling T2 control  chart, signal  out of control